2004
DOI: 10.1021/ja046067u
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of Artificial Photosynthetic Reaction Centers in Liquid Crystals Probed by Multifrequency EPR (9.5 and 95 GHz)

Abstract: Photoinduced charge separation and recombination in a carotenoid-porphyrin-fullerene triad C-P-C(60)(1) have been followed by multifrequency time-resolved electron paramagnetic resonance (TREPR) at intermediate magnetic field and microwave frequency (X-band) and high field and frequency (W-band). The electron-transfer process has been characterized in the different phases of two uniaxial liquid crystals (E-7 and ZLI-1167). The triad undergoes photoinduced electron transfer, with the generation of a long-lived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 73 publications
7
58
0
Order By: Relevance
“…For weakly coupled donor-acceptor systems as the triads under investigation, as already demonstrated for the C-P-C60 triad bearing the tetraalkylporphy¡ bridge [18], the electronic coupling element VDA is notable to contrast the retardation effect produced by the nematic potential on the longitudinal relaxation time r L. The adiabacity factor ~c, which describes the transition from the nonadiabatic to the solvent-controlled adiabatic limit is a function of both V2A and r L [52]:…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…For weakly coupled donor-acceptor systems as the triads under investigation, as already demonstrated for the C-P-C60 triad bearing the tetraalkylporphy¡ bridge [18], the electronic coupling element VDA is notable to contrast the retardation effect produced by the nematic potential on the longitudinal relaxation time r L. The adiabacity factor ~c, which describes the transition from the nonadiabatic to the solvent-controlled adiabatic limit is a function of both V2A and r L [52]:…”
Section: Discussionmentioning
confidence: 80%
“…The radical pair spectral analysis was performed using programs written in MatLab, based on the theoretical description of nondiffusing spin-correlated radical pairs, in the high field approximation [18,34].…”
Section: Trepr Spectra Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context it is to be mentioned that in the cases of some triad systems of carotenoidporphyrin-fullerene and porphyrin-tetrathiafulvalene-fullerene, Valentin et al [50,51] observed that when these are embedded in LC medium, all the important features of photochemistry observed before in the isotropic solvents remain conserved. Similar investigations in the pseudo-ordered domain of 5CB with the other organic dyad systems are under progress.…”
Section: Transient Absorption Measurementsmentioning
confidence: 98%
“…In recent years, various linked organic electron donor-acceptor dyad and multichromophoric systems have been synthesized [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Within the dyad systems, multi-step electron transfer reactions, which mimic the charge-separations in natural photosynthesis, occur.…”
Section: Introductionmentioning
confidence: 99%